Effect of passive finger exercises on grip strength and the ability to perform activities of daily living for older people with dementia: a 12-week randomized controlled trial - Liu BB (Dove Medical Press, 2018)
Bingbing Liu,1 Xueping Chen,1 Yang Li,1 Hui Liu,2 Shasha Guo,2 Ping Yu3 1Nursing Department, Qianjiang College, Hangzhou Normal University, Hangzhou, China; 2Medicine Department, Hangzhou Normal University, Hangzhou, China; 3School of Computing and Information Technology, Faculty of Engineering and Information Sciences, University of Wollongong, Wollongong, NSW, Australia Background: Dementia adds burden to society. As it is not curable, physical exercise activities are optimal to improve the physical strength and quality-of-life of people with dementia. Aim: Design, implementation, and examination of a set of passive finger exercises and their effects on improving grip strength and activities of daily living (ADL) for older people with dementia. Methods: Forty older people with dementia were recruited and randomly allocated into an experimental group and a control group, each with 20 people. The control group received routine nursing care. In addition to this, the experimental group received 25-minutes of passive finger exercises every day for 12 weeks. The health outcomes measured were grip strength and ADL, before and after the intervention. Grip strength was assessed by electrical hand muscle dynamometer. ADL were assessed with Barthel index. Results: Although there was no effect on grip strength, passive finger exercises led to significant improvements in urinary control, defecation function, and overall ADL in comparison with the control group. Implications for practice: Passive finger exercises can be integrated into physical exercise programs for older people with dementia to improve their urinary control, defecation function, and ADL. Keywords: physical exercise, passive finger exercise, grip strength, urinary control, defecation, activities of daily living, ADL, dementia